1999
DOI: 10.1143/jjap.38.3322
|View full text |Cite
|
Sign up to set email alerts
|

Operating Characteristics of a Same-Phase Drive-Type Ultrasonic Motor Using a Flexural Disk Vibrator

Abstract: In this paper we describe an ultrasonic motor using a flexural disk vibrating in two degeneration modes driven by a same-phase input signal. Its operating characteristics depend considerably on the pressing force between the stator and the rotor. We report some experimental studies of this effect. Measurements of the vibration mode showed that the change in the rotational direction of the motor was caused by a shift in the vibration axis of the mode synthesized from two degeneration mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Bi-directional ultrasonic motors using mode coupling between the longitudinal and bending modes caused by the asymmetry shape (Aoyagi and Tomikawa, 1993; Aoyagi et al, 1992; Tamura et al, 2007) or crystal anisotropy (Tamura et al, 2008, 2010) of the stator were reported; the coupling effect could provide a pair of modes by asymmetry shape or crystal anisotropy; coupling mode is allotted to push the load in each direction; however, the output performances are not equal in each moving direction. Utilizing two same bending modes of a circle stator (Aoyagi et al, 2002; Takano et al, 1992, 1994, 1999), the same output performances in reverse direction were obtained; however, this type of structures was not suitable for effectively moving a linear slider directly.…”
Section: Working Principles and Configurationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Bi-directional ultrasonic motors using mode coupling between the longitudinal and bending modes caused by the asymmetry shape (Aoyagi and Tomikawa, 1993; Aoyagi et al, 1992; Tamura et al, 2007) or crystal anisotropy (Tamura et al, 2008, 2010) of the stator were reported; the coupling effect could provide a pair of modes by asymmetry shape or crystal anisotropy; coupling mode is allotted to push the load in each direction; however, the output performances are not equal in each moving direction. Utilizing two same bending modes of a circle stator (Aoyagi et al, 2002; Takano et al, 1992, 1994, 1999), the same output performances in reverse direction were obtained; however, this type of structures was not suitable for effectively moving a linear slider directly.…”
Section: Working Principles and Configurationsmentioning
confidence: 98%
“…The theory of two in-plane modes of a ring excited by a single-phase drive was discussed (Cagatay et al, 2003; Koc et al, 2000, 2002; Peter, 1987; Sashida, 1982; Ueha et al, 1993). Tubular ultrasonic motors utilizing only one drive signal were developed (Aoyagi et al, 2002; Cagatay et al, 2003; Chen et al, 2015; Friend et al, 2003; Ishii et al, 1993; Koc et al, 2000, 2002; Ma et al, 2016; Takano et al, 1992, 1994, 1999; Tamura et al, 2010; Ueha et al, 1993); This motor has two orthogonal degenerative bending modes, and only one excitation signal was supplied to one PZT element at a frequency between the resonance frequencies of the two modes, activating both modes and providing oscillating movement. The rotation direction could be reversed by changing the voltage to the other PZT element.…”
Section: Working Principles and Configurationsmentioning
confidence: 99%
“…For example, Sashida [11] used an oblique elasticity slice located at one end of a Langevin vibrator to transform the vibrator's longitudinal vibration into oblique elliptical vibration of the driving foot to achieve unidirectional rotary movement. Takano et al [12] developed a flexural disk that vibrates in two degradation modes to generate the ideal movement under a single-phase drive. In addition, the concept of single-phase asymmetric excitation with symmetric structure was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same-form degenerated bending modes of a stator disk with projection teeth, the singlephase driving and same characteristics in reverse operation were obtained. [22][23][24][25] The projection teeth generate a driving force in the circumferential direction to rotate the disk rotor whose center is aligned with the stator disk. This structure is not suitable to effectively move a linear slider directly.…”
Section: Introductionmentioning
confidence: 99%